(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The article analyzes the role and significance of the Enlightenment ideas of the jadids in the development of Eastern educational philosophy on the basis of the study of scientific philosophical literature and primary sources. Religious values and categories were reworked in secular content by the Jadid enlightenment. In order to reform the education system, the jadids began to create their own national schools, where education was carried out on the basis of new methods. The jadids expressed their awareness of the essence of European modern educational technologies through the concept of their educational philosophy, as well as their ability to effectively apply them to the national educational system, as well as their national creative approach to the organization of the educational process.